PENINGKATAN KETERAMPILAN MENULIS CERPEN BERBASIS KUIK (KISAH, UNSUR INTRINSIK, DAN KHAYALAN) MELALUI MODEL SINEKTIK DI KELAS X SMA NEGERI 1 PEMALANG - Amitaningsih, Amitaningsih (English Department FBS UNP, 2011)
This classroom action research is aimed to improve the skills of writing short stories based KUIK through the application of sinectics model in class X SMA Negeri 1 Pemalang. The research was conducted on 37 students in class X SMA 1Pemalang. Quantitative data collection is carried out through tests to write the short stories, then it was analyzed by using descriptive analysis of the percentage. Qualitative data collection used manual observation, interviews, and documentation to uncover changes in behavior of students in the learning process. The findings showed the average value before the action research by 59.7%, and the average value of 79.4% after the action. It shows that a sinectics model can improve KUIK-based short stories writing skill by 19,7 %Â in SMA Negeri 1 Pemalang students. Keyword: writing skill, KUIK, short story, sinectics model